PERSON JOB FIT, KOMPETENSI DAN LINGKUNGAN KERJA TERHADAP JOB SATISFACTION PEGAWAI PADA DINAS KOPERASI DAN TENAGA KERJA KABUPATEN BOYOLALI - Muhammad Muchlis Hidayat (Fakultas Ekonomi dan Bisnis UTP Surakarta, 2020)
This study aims to determine the effect of partially and simultaneously person job fit, competence, and work environment on employee job satisfaction at Dinas Koperasi Dan Tenaga Kerja Kabupaten Boyolali. This type of research is descriptive quantitative. The population in this study were all of the 40 employees of Diskopnaker in Boyolali Regency. The total sampling technique used in this study with the sample used from the entire population of 40 respondents. The method used is multiple linear regression analysis, data collection techniques by distributing questionnaires. The results of this study that simultaneously variable person job fit, competence and work environment have a positive and significant effect on job satisfaction. Evidenced by the results of the F test showed a calculation of Fhitung 35,970 > Ftable 2,64. T-test results partially person job fit affect job satisfaction, competence variables and work environment partially do not affect job satisfaction. Coefficient of determination R2 obtained Adjusted R Square value of 0,546 means that the variables used in this study influence 54,6% of job satisfaction at Diskopnaker Kabupaten Boyolali.